Potential Common Genetic Risks of Sporadic Parkinson’s Disease and Amyotrophic Lateral Sclerosis in the Han Population of Mainland China - Lu, Yi; Chen, Wenzhi; Wei, Caihui; Zhu, Yu; Xu, Renshi (Frontiers in Neuroscience, 2021)
Sporadic Parkinson disease (sPD) and amyotrophic lateral sclerosis (sALS) are neurodegenerative diseases characterized by progressive and selective neuron death, with some genetic similarities. In order to investigate the genetic risk factors common to both sPD and sALS, we carried out a screen of risk alleles for sALS and related loci in 530 sPD patients and 530 controls from the Han population of mainland China (HPMC). We selected 27 single nucleotide polymorphisms in 10 candidate genes associated with sALS, and performed allelotyping and genotyping to determine their frequencies in the study population as well as bioinformatic analysis to assess their functional significance in these diseases. The minor alleles of rs17115303 in the DAB adaptor protein 1 (DAB1) gene and rs6030462 in the protein tyrosine phosphatase receptor type T (PTPRT) gene were correlated with increased risk of both sPD and sALS. Polymorphisms of rs17115303 and rs6030462 were associated with alterations in transcription factor binding sites, secondary structures, long noncoding RNA interactions, and nervous system regulatory networks; these changes involved biological processes associated with neural cell development, differentiation, neurogenesis, migration, axonogenesis, cell adhesion, and metabolism of phosphate-containing compounds. Thus, variants of the DAB1 gene (rs17115303) and PTPRT gene (rs6030462) are risk factors common to sPD and sALS in the HPMC. These findings provide insight into the molecular pathogenesis of both diseases and can serve as a basis for the development of targeted therapies.